Erôs and the Polis (BICS Supplements, 2019)
Arising out of a conference on ‘Erôs in Ancient Greece’, the articles in this volume share a historicizing approach to the conventions and expectations of erôs in the context of the polis, in the Archaic and Classical periods of ancient Greece. The articles focus on (post-Homeric) Archaic and Classical poetic genres – namely lyric poetry, tragedy, and comedy – and some philosophical texts by Plato, Xenophon, and Aristotle. They pursue a variety of issues, including: the connection between homosexual erôs and politics; sexual practices that fell outside societal norms (aristocratic homosexuality, chastity); the roles of sôphrosynê (self-control) and akrasia (incontinence) in erotic relationships; and the connection between erôs and other socially important emotions such as charis, philia, and storgê. The exploration of such issues from a variety of standpoints, and through a range of texts, allows us to place erôs as an emotion in its socio-political context.